Job Satisfaction as a Mediator of Justice towards Organizational Citizenship Behavior - Alfato Yusnar Kharismasyah; Bima Cinintya Pratama; Fatmah Bagis (Benefit: Jurnal Manajemen dan Bisnis, 2017)
Time goes rapidly and competition is getting tougher. It demands employees to give high performance in order to exceed work standard determined by the company. work system innovation in banking companies provide stimuli for employees both from basic employees to management level to always be active in and have advantages in understanding the job desk. Extra ordinary behavior, which is usually called. Organizational Citizenship Behavior, is expected to change mindset where employees do not only master one ability, but several abilities or skills beyond their job description. Therefore, the purpose of this study is to analyze the influence of Distributive and Procedural Justice on OCB through Job satisfaction. This research is descriptive and verivicative analysis. Descriptive research was conducted to obtain a description of Distributive Justice, Procedural Justice, Job satisfaction, and OCB. While verivicative research is done to know the relationship between variables through the calculation - statistical calculation. The method used is survey method. While the sampling technique is Saturated / Census Samples with 65 respondents. Data analysis in this study using the analysis of PLS (Partial Least Square) and found that the Distributive Justice, Procedural Justice has a significant influence on Job Satisfaction that impact on OCB. There are several researchers who have researched OCB from a human resource point of view. Contribution of this research is to help managers to formulate strategies and policy implementation related to the proper management of Human Resources And create new Human Resources with all the best ability to play an extra role in doing the job.